Collision Tumors: Pancreatic Adenocarcinoma and Mantle Cell Lymphoma - Dasanu, Constantin A; Shimanovsky, Alexei; Rotundo, Edyta K; Posteraro, Anthony F; Cooper, Dennis L; Atienza, Jonessa A (JOP. Journal of the Pancreas, 2013)
Context Collision tumors are very rare entities composed of two or more distinct tumor components, each separated by normal tissue. Perhaps due to technical advances in the last decade, the incidence of collision tumors has been on the rise. To the best of our knowledge, collision tumors featuring mantle cell lymphoma and pancreatic adenocarcinoma have not been previously described in the scientific literature. Case report For the first time, we describe herein the clinical course of a collision tumor between pancreatic adenocarcinoma and mantle cell lymphoma. Discussion We hypothesize several aspects in the pathogenesis of a such event and review the existing literature on collision tumors. Image: PET/CT scan showing extensive FDG-avid tumor featuring.